СТРУКТУРНО-СЕМАНТИЧЕСКИЕ И ТИПОЛОГИЧЕСКИЕ ОСОБЕННОСТИ ЭКОЛОГИЧЕСКИХ ТЕРМИНОВ В КАРАКАЛПАКСКОМ И АНГЛИЙСКОМ ЯЗЫКАХ - Шаниязов, Б.Ж.; Отенова, Ф.Т.; Уразбаева, А. (SCIENCE and SOCIETY, 2016)
The article deals with the structural-semantic and typological peculiarities of ecological terms, their lexical meaning and common use in languages belonging, to different systems. The author of the article also studies the synonymy in terminology.